2017
DOI: 10.1371/journal.pone.0175896
|View full text |Cite|
|
Sign up to set email alerts
|

Under threat by popular vote: German-speaking immigrants’ affect and cognitions following the Swiss vote against mass immigration

Abstract: A popular initiative in support of regulating future immigration to Switzerland was accepted by the electorate in 2014. Assuming that the initiative acted as an exclusionary threat for current immigrants of Switzerland, we conducted an online survey among a sample of highly-skilled German-speaking immigrants (“expats”). Participants reported having experienced negative affect following the vote. Moreover, having a more left-wing orientation, living in a political constituency that had voted pro-regulation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 80 publications
0
10
0
1
Order By: Relevance
“…Our respective theoretical assumptions rely heavily on assumptions derived from theoretical models about ostracism as well empirical laboratory studies (Williams, 2009). Based on these, we expect a positive association between ostracism and the experience of threat (indicated by measures of emotions and self-esteem; Hawkley et al, 2010;Sebastian et al, 2010;Williams, 2009) and a negative association between ostracism and life satisfaction (Gilman et al, 2013;Rudert, Janke, et al, 2017). Finally, we expect maladaptive associations between ostracism and social behavior, particularly positive associations with hostile behavior (indicated by higher negative and lower positive reciprocity and a lower tendency to forgive; Twenge et al, 2007;Twenge et al, 2001) as well as withdrawal tendencies (Ren et al, 2016; indicated by one's number of close friends as well as engagement in social activities).…”
Section: Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our respective theoretical assumptions rely heavily on assumptions derived from theoretical models about ostracism as well empirical laboratory studies (Williams, 2009). Based on these, we expect a positive association between ostracism and the experience of threat (indicated by measures of emotions and self-esteem; Hawkley et al, 2010;Sebastian et al, 2010;Williams, 2009) and a negative association between ostracism and life satisfaction (Gilman et al, 2013;Rudert, Janke, et al, 2017). Finally, we expect maladaptive associations between ostracism and social behavior, particularly positive associations with hostile behavior (indicated by higher negative and lower positive reciprocity and a lower tendency to forgive; Twenge et al, 2007;Twenge et al, 2001) as well as withdrawal tendencies (Ren et al, 2016; indicated by one's number of close friends as well as engagement in social activities).…”
Section: Research Questionsmentioning
confidence: 99%
“…Consequently, certain exclusion experiences that are perceived as unfair by younger adults might be perceived as acceptable and in line with social norms by elder adults (e.g., exclusion related to traditional gender roles). Such differences might subsequently influence how individuals experience social exclusion (Rudert & Greifeneder, 2016;Rudert, Janke, et al, 2017).…”
Section: Older Adults Experience Ostracism Less Frequentlymentioning
confidence: 99%
“…Additionally, they …nd that high-skilled foreigners were the most sensitive to the vote in terms of their location choice decisions. Rudert et al (2017) also …nd evidence of a strong e¤ect of the vote on high-skilled migrants' self-reported life satisfaction and attitudes towards Switzerland. If high-skilled foreign migrants also have high levels of bridging identity, these …ndings are consistent with the predictions of the model.…”
Section: Identity Shocksmentioning
confidence: 84%
“…Nicht jeder Ausschluss Anderer hat direkt eine bösartige oder zurechtweisende Intention. In grösseren Organisationen mit viel Arbeitsteilung kann es beispielsweise zu Ausschluss aufgrund bestimmter Rollenverteilungen oder Normen innerhalb der Organisation kommen (Rudert & Greifeneder, 2016 (Schoel, Eck, & Greifeneder, 2014) Allgemeinen ablehnten, umso stärker fühlten sie sich in Folge der Abstimmung persönlich bedroht (Rudert, Janke, & Greifeneder, 2017).…”
Section: Soziale Ausgrenzung In Organisationenunclassified